MO787USE OF THE PREVENTIVE HAEMOSTASIS IN SURGICAL COMPLICATIONS OF VASCULAR ACCESS. (29th May 2021) - Corciulo, Simone; Covella, Bianca; Rossi, Luigi; Lomonte, Carlo
Abstract: Background and Aims: Arteriovenous fistula (AVF) is currently the recommended vascular access type and its preservation is required to ensure a safe treatment for HD patients. Nevertheless, reinterventions are often needed to treat life threatening complications such as eschars, aneurysms, high flow.These surgical procedures are at high risk of bleeding, time-consuming and technically demanding. Here we describe our approach by using preventive hemostasis to treat different types of AVF complications, such as aneurysmectomy, high flow fistula correction, ulcerectomy. Method: The technique consists of a few steps. First, regional anesthesia is performed by brachial plexus nerve block and intravenous antibiotic prophylactic therapy is administered. Then, an inflatable tourniquet is placed on the arm, proximally to the elbow joint, after wrapping the site with a soft gauze to prevent postoperative discomfort and bruising due to accidental pinch of the skin. The arm is then elevated to allow passive exsanguination and a 5" Esmarch bandage is applied from the hand to the tourniquet cuff. The methodical application of the Esmarch bandage requires an assistant to hold the arm properly in the upright position. Once the bandage is applied, the tourniquet is inflated to complete the exsanguination of the extremity. The inflation pressure has to be adapted to patient systolic pressure, generally a 'suitable' pressure for an upper limb tourniquet is 250-300 mmHg. Lastly, the Esmarch bandage is unwrapped and, after sterile surgical draping, it is possible to proceed to skin incision. Results: From Jan 2019 to Dec 2020, we enrolled 9 patients with AVF complications treated with the preventive emostasis. The mean age of the patients was 62 years (range, 45-80 years). Table 1 shows types of AVFs and complications, performed revisions, outcomes, short and long term complications. The tourniquet average time of application was 29 + 7, 7 min. Preventive hemostasis ensures absence of blood loss, even during high flow access revision. In one patient, a moderate subcutaneous hemorrhage occurred 8 hours after the end of the surgical procedure, requiring further revision. No vascular or soft tissue complications were reported except for temporary dysesthesias. Conclusion: Our experience shows that preventive haemostasis offers several advantages for surgeons and patients, allowing a clear operative field and avoidance of application of clamps, prevents blood loss, and reduce the need for blood transfusion. Furthermore, reperfusion injury risk is minimized. The only complication occurred suggests the recommendation to suture skin incision after removing the tourniquet to reduce risk of postoperative bleeding. In conclusion, the technique is reliable and safely applicable to surgical treatment of vascular access complication.